2021
DOI: 10.1093/nar/gkab640
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous piRNA-guided slicing triggers responder and trailer piRNA production from viral RNA inAedes aegyptimosquitoes

Abstract: In the germline of animals, PIWI interacting (pi)RNAs protect the genome against the detrimental effects of transposon mobilization. In Drosophila, piRNA-mediated cleavage of transposon RNA triggers the production of responder piRNAs via ping-pong amplification. Responder piRNA 3′ end formation by the nuclease Zucchini is coupled to the production of downstream trailer piRNAs, expanding the repertoire of transposon piRNA sequences. In Aedes aegypti mosquitoes, piRNAs are generated from viral RNA, yet, it is un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…This results in piRNA sharp ends and a so-called +1U bias. Importantly, analysis of vpiRNAs from Aag2 cells infected with the alphavirus Sindbis (SINV) had suggested a Zucchini-like biogenesis mechanism in vpiRNA 3’ termini formation, as sharp ends and +1U bias were observed [ 52 ]. This led us to further investigate the origins of 21 nt vsi-piRNAs by subjecting vpiRNAs (25–30 nt) and 21 nt vsi-piRNAs sequences to a similar analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in piRNA sharp ends and a so-called +1U bias. Importantly, analysis of vpiRNAs from Aag2 cells infected with the alphavirus Sindbis (SINV) had suggested a Zucchini-like biogenesis mechanism in vpiRNA 3’ termini formation, as sharp ends and +1U bias were observed [ 52 ]. This led us to further investigate the origins of 21 nt vsi-piRNAs by subjecting vpiRNAs (25–30 nt) and 21 nt vsi-piRNAs sequences to a similar analysis.…”
Section: Resultsmentioning
confidence: 99%
“…They may be products of vpiRNA degradation, perhaps post-processing by the recently identified Ae . aegypti ortholog of Zucchini, and/or by the corresponding ortholog Nibbler which has 3’-5’ exonuclease activity [ 52 ]. However, this would require further studies, such as silencing the expression of these proteins followed by small RNA sequence analysis.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti , Piwi5 and Ago3 are the core components of the ping-pong amplification mechanism that generates vpiRNAs following Sindbis virus infection [ 107 ]. Piwi4, on the other hand, was not found to be required for the ping-pong amplification mechanism [ 110 ]. Interestingly, knockdown of Piwi4 can result in an increase of production of primary/initiator piRNAs from piRNA clusters that is controlled by Piwi5, indicating competition between the actions of both Piwi proteins [ 110 ].…”
Section: Insights From Research On Piwi Proteins and Pirnas In Mosqui...mentioning
confidence: 99%
“…Whereas secondary piRNAs are produced only in germ cells by secondary expansion of Argonaute 3 (AGO3) protein with Aub-piRISCs. This process is also known as the ping-pong pathway [ 6 , 9 , 10 , 11 ]. Recent studies demonstrated that piRNAs, as newly emerging regulators of gene expression, could exert functions in an array of biological processes such as immune response and development [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%